Media and Journalists in Twitter: The Chilean Case - López-Hermida Russo, Alberto (2011)
Social networks like Twitter have become platforms used by people as well as corporations to reach audiences of a size that, barely a decade ago, seemed unimaginable. Journalism has also been affected by this trend, so now journalists and media corporations make use of these social networks.